I share, therefore I know? Sharing online content ‐ even without reading it ‐ inflates subjective knowledge - Ward, Adrian F.; Zheng, Jianqing (Frank); Broniarczyk, Susan M. (Journal of Consumer Psychology, 2023)
AbstractBillions of people across the globe use social media to acquire and share information. A large and growing body of research examines how consuming online content affects what people know. The present research investigates a complementary, yet previously unstudied question: how might sharing online content affect what people think they know? Sharing signals expertise, and people frequently internalize their public behavior into their private self‐concepts. We therefore posit that sharing information on social media may cause people to believe they are as knowledgeable as their posts make them appear. We examine this possibility in the context of “sharing without reading,” a phenomenon that allows us to isolate the effect of sharing on subjective knowledge from any influence of reading or objective knowledge. Six studies provide correlational (study 1) and causal (studies 2, 2a) evidence that sharing—even without reading—increases subjective knowledge, and test the internalization mechanism by varying the degree to which sharing publicly commits the sharer to an expert identity (studies 3–5). A seventh study investigates potential consequences of sharing‐inflated subjective knowledge on downstream behavior in the domain of financial decision‐making.